2012
DOI: 10.1177/1468087412437507
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a novel mild air hybrid engine technology, RegenEBD, for buses and commercial vehicles

Abstract: In this paper, a novel cost-effective mild air hybrid engine concept for buses and commercial vehicles, RegenEBD, is presented. This air hybrid technology is designed to convert kinetic energy into pneumatic energy of the compressed air stored in the air tank normally installed on such vehicles. The compressed air can then be used to drive an air starter to achieve regenerative stop–start operations for buses and delivery vehicles with frequent stop–start operations. For other commercial vehicles, it can provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…This provides the basis of the engine response map of the compressor mode operation comprising engine braking torque values as a function of throttle positions, which has been used for the vehicle driving cycle analysis. 10,11…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This provides the basis of the engine response map of the compressor mode operation comprising engine braking torque values as a function of throttle positions, which has been used for the vehicle driving cycle analysis. 10,11…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…Therefore, it has confirmed that the use of an intake throttle can be an effective means to controlling the engine braking torque in the air hybrid engine operations. This provides the basis of the engine response map of the compressor mode operation comprising engine braking torque values as a function of throttle positions, which has been used for the vehicle driving cycle analysis [10,11]. Table 4 shows an engine response map which summarises the tank pressure and the intake throttle valve opening as functions of the flow rate (g/cycle) of air mass charged for the engine speed range between 1000 and 2000 rpm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Andersson et al focused on using pressurized air instead of atmospheric air for cylinder charging [4]. Lee et al proposed a hybrid pneumatic power train in which two shutoff valves connected to a convenient access hole in the engine cylinder enable the cylinder to operate as a regenerative compressor and expander when required [5]. Tai et al utilized four fully-flexible camless valves (two intakes and two exhausts) for each cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation showed that the pneumatic hybridisation could recover about 10% of total energy under different conditions. Lee et al 2325 studied a cost-effective mild hybrid pneumatic engine concept for buses and commercial vehicles. The simulation showed that the fuel mass consumed during the New European Driving Cycle (NEDC) was 677 g for a standard vehicle and 631.2 g for a hybrid pneumatic vehicle, indicating a fuel saving effect of 6.8%.…”
Section: Introductionmentioning
confidence: 99%